Comparison of the Spectrum of Radiologic and Clinical Manifestations of Pulmonary Disease Caused by Mycobacterium avium Complex and Mycobacterium xenopi. Issue 3 (August 2014) - Carrillo, Maria C.; Patsios, Demetris; Wagnetz, Ute; Jamieson, Frances; Marras, Theodore K.
Aim: Mycobacterium xenopi is described with upper lobe cavitation ("fibrocavitary" pattern), whereas the Mycobacterium avium complex (MAC) is described with bronchiectasis and centrilobular nodules ("nodular bronchiectasis"). We retrospectively described and compared computed tomography (CT) chest manifestations of disease caused by MAC and M xenopi . Materials and Methods: We reviewed patients who had either MAC or M xenopi lung disease and who had CTs between January 2002 and December 2003. Clinical data were recorded, and the patterns on chest CTs were categorized as "fibrocavitary, " "nodular bronchiectatic, " and "unclassified." Results: There were 74 patients; 50 with MAC and 24 with M xenopi . The patients with MAC were older (mean 69 vs 58 years; P = .007). Patients with M xenopi more often had emphysema (50% vs 20%; P = .02), cavities (46% vs 16%; P = .01), and nodules ≤5 mm (88% vs 58%; P = .02). M xenopi cases more commonly had a fibrocavitary radiologic pattern (33% vs 18%), with no statistically significant difference ( P = .24). MA C was more often associated with a nodular bronchiectatic pattern (68% MAC vs 4% M xenopi ; P < .0001). Sixty-three percent of patients with M xenopi had a pattern that was predominantly randomly distributed nodules (11/15 [73%]) or consolidation and/or ground-glass opacities (4/15 [27%]). Conclusion: Compared with MAC, patients with M xenopi infection develop more cavities and more nodules, and they less often have a predominant nodular bronchiectatic pattern. Although a predominantly cavitary pattern appears to be more common with M xenopi, the majority of patients with M xenopi had CT patterns of random nodules or consolidation and/or ground-glass opacities rather than classically described findings.